PENERAPAN MULTIMEDIA INTERAKTIF WORDWALL UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN KELAS ll DI SDN KALISALAM ll - Nur Afrika Lita Dewi; Lutfi Arya Wardana; Didit Yulian Kasdriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted based on the background of this study discussing the importance of learning media, especially Wordwall interactive media, in increasing the interest, motivation, understanding of concepts, and learning outcomes of grade II students of SDN Kalisalam II on addition and subtraction materials. Learning media functions as an introductory tool that is able to convey messages in an interesting and adaptive manner, and arouse the interest of students so that the learning process becomes more effective. This research has found several problem formulations contained in increasing interest in learning in class II SDN Kalisalam 2 Probolinggo Regency on addition and subtraction material. There are values obtained by students ranging from 50 to 65 while the value that reaches the completeness criteria is 70. So, in the implementation of this pre-test it was declared incomplete and there were still many students who scored below the average. By applying wordwall interactive multimedia learning media on addition and subtraction material, the percentage results found in cycle ll are the number of complete students 7 children (33.33%), there are 6 students (23.80%). In cycle ll there was an increase with 10 students who were complete (76.92%), and 3 children (47.61%) were not complete. This study aims to increase the learning interest of grade ll students at SDN Kalisalam ll, Probolinggo Regency in addition and subtraction materials using wordwal interactive multimedia. For this reason, researchers conducted research that aims to activate student learning and to increase student interest in learning improvements carried out by researchers. Research using the Classroom Action Research (PTK) method is an observation of learning activities in the form of an action that is deliberately presented and occurs in the classroom simultaneously Researchers can collect data that cannot be revealed through surveys or observations. The results of this research are very useful, especially for educators and learners, as it allows for the continued use of this learning exercise in mathematics or other topics.